Nonsyndromic oligodontia associated with submerged primary molars: Clinical features and management protocols - Mahesh Ramakrishnan; Kanimozhi Gandeeban (Wolters Kluwer Medknow Publications, 2014)
Tooth agenesis is the most common dental anomaly. The agenesis of permanent teeth can seriously affect children both physically and emotionally, especially during the years of transition into adolescence. This clinical report illustrates the oral rehabilitation of 12-year-old patient with multiple congenitally missing teeth using removable denture. The presented case reports an unusual occurrence of multiple missing teeth in a nonsyndromic patient and the treatment protocol for managing these conditions. This case is significant in three ways. First being a nonsyndromic case of missing 15 permanent teeth. Second a rare case of missing first maxillary permanent molars and third being the presence of bilateral submerged tooth.